Don't blame me: The effects of CEO power, board affiliation, and Sarbanes-Oxley on CEO turnover following financial misrepresentation - GOMULYA, David (Institutional Knowledge at Singapore Management University, 2011)
I examine the conditions under which CEOs are terminated as an outcome of firm financial restatements. I find that chief executive‘s power acts to limit terminations,especially in cases of more severe restatements, while board members most closely affiliated with the CEO appear to avoid the stigma of financial restatements by deflecting blame to the CEO, increasing terminations. I also examine the effectiveness of regulatory remedies such as Sarbanes-Oxley, aimed at strongly penalizing CEOs for financial misrepresentation. Sarbanes-Oxley significantly alters the relationship between CEOs and their board. My context is restating U.S. public firms before (1995-1998) and after Sarbanes-Oxley (2003-2006).